‘QRIS Cross Border’ as Digital Financial Inclusion Acceleration in Southeast Asia - bani rachmad, Atsal amar; Raharjo, Maritza (Global Local Interactions: Journal of International Relations, 2023)
This study aims to examine economic issues in a number of countries, specifically the number of unbanked individuals who contribute to economic stagnation. In addition, several Southeast Asian nations have begun to adopt digital financial services (digital finance). Digital Financial Inclusion has positive effects on MSMEs, including financial transactions and documenting transactions, obtaining financial assistance from bank and non-bank institutions, and digital finance is viewed as more reliable by the public due to its reliance on artificial intelligence. The development of QRIS, which began in Indonesia, is anticipated to result in digital economic adjustments for Southeast Asian nations. This study employs descriptive qualitative methodology, which describes extant phenomena. The findings of this study indicate that the application of digital finance, particularly QRIS as a game-changer, can increase efficiency and make cross-border payments more inclusive. Due to the existence of QRIS, the community is able to make cross-border remittances and increase the country's foreign exchange and trade balance.